Dusp4 Contributes to Anesthesia Neurotoxicity via Mediated Neural Differentiation in Primates - Yan, Jia; Li, Jingjie; Cheng, Yanyong; Zhang, Ying; Zhou, Zhenning; Zhang, Lei; Jiang, Hong (Frontiers in Cell and Developmental Biology, 2020)
Background: Children with multiple exposures to anesthesia and surgery may undergo cognitive impairment during development. Anesthesia has been revealed to induce cognitive deficiency in young rodent and monkey. However, there is still largely unknown about the molecular mechanism of the sevoflurane in neural development toxicity. Methods: Here we combined RNA sequencing analysis of macaque’s prefrontal cortex and human neural differentiation to investigate the mechanism of sevoflurane-induced neurotoxicity in primate. Results: The level of dual specificity protein phosphatase 4(Dusp4) was significantly downregulated in non-human primate after sevoflurane treatment. We further uncovered the dynamical expression of Dusp4 during the human neural differentiation of human embryonic stem cells and found that knockdown of Dusp4 could significantly inhibit the human neural differentiation. Conclusion: This study indicated that Dusp4 is critically involved in the sevoflurane-induced inhibition of neural differentiation in non-human primate and the regulation of human neural differentiation. It also suggested Dusp4 could be the potential therapeutic target for preventing the sevoflurane-induced neurotoxicity in primate.